SISTEM GOTONG ROYONG BERGILIR DALAM PENGELOLAAN PESANGGRAHAN MBAH MBUTOH RADEN DANANG PATI (Unnes Civic Education Journal, 2022)
A local cultural wisdom is a precious asset which have to preserve by us. For the example is Pesanggrahan (guesthouse) Mbah Mbuton Raden Danang which is located in Gendol sub-village, Mojomulyo village, Tambakromo district, Pati regency. Conveying an incorrect culture makes the guesthouse unmanaged. Many conflicts behind, this is why a mutual cooperation in rotating is implemented to solve the problems. The purpose of this research are (1) to find out the factors behind the abandonment of the guesthouse. (2) to look for the exact solutions. (3) to give a knowledge and understanding about the importance of loving historical heritage. (4) to know the values behind in managing the guesthouse process. This research used qualitative approach. Data sources obtained by primarly data and secondary data through informant, photo, and literature. The technique used in collecting data were observation, interview, and documentation. The data was analized through collecting data, data reduction, serving data, and conclusion. The result of the reserch showed that it used qualitative approach. The data sources took from primarly data and secondary data through informant, photo, and literature. The technique used in collecting data were observation, interview, and documentation. The data was analyzed by collecting data, data reduction, serving data, and conclusion. The result of study showed 1) the awarness is low related to the love of historical heritage; (2) that is not place to develop knowledge about history; (3) there are pros and cons related to the management of the guesthouse; (5) the limitations in managing funds and infrastructure.